Cu2O‐Decorated Mesoporous TiO2 Beads as a Highly Efficient Photocatalyst for Hydrogen Production. Issue 1 (31st October 2013) - Cheng, Wei‐Yun; Yu, Tsung‐Hsuan; Chao, Kang‐Ju; Lu, Shih‐Yuan
Abstract Cu2O‐decorated mesoporous TiO2 beads (MTBs) are developed as a low‐cost, highly efficient photocatalyst for H2 production. MTBs with a high specific surface area of 189 m2 g−1, a large pore volume of 0.43 cm3 g−1 and a suitable pore size of 8.9 nm are decorated with band‐structure‐matched Cu2O nanocrystals through a simple, fast and low‐cost chemical bath deposition process. The Cu2O nanocrystals serve as an electron–hole separation centre to promote H2 evolution. Under optimal operation conditions, an ultra‐high specific H2 evolution rate of 223 mmol h−1 g−1 is achieved. The success is attributed to the structural advantages of the MTBs of high specific surface areas, large pore volumes and suitable pore sizes together with the much improved electron–hole separation and light utilisation of the Cu2O‐decorated MTBs. The H2 evolution rates achieved with the Cu2O‐decorated MTBs are one order of magnitude higher than those achieved by commercial P25 TiO2.